A Single Case Study On The Ayurvedic Management Of Subclinical Hypothyroidism - Akbar, Waquar; Moniruzzaman, Md; Mahapatra, P B Kar (International Research Journal of Ayurveda & Yoga, 2021)
The number of cases of hypothyroidism is increasing day by day resulting in discomforts, sign and symptoms such as weight gain, dry skin, bradycardia , hair loss , irregular menstruation in females, etc. In Ayurveda we did not find any vyadhi having direct correlation with hypothyroidism , so as per acharya Charaka it may be treated as a anukta vyadhi , on the basis of prakriti, hetu, rupa and others. As per the symptoms of hypothyroidism it can be predicted that there are involvement of kapha and vata dosa, so it should be managed as a kapha vataja vyadhi. The present study deals with a female patient, aged 35 years , suffering from sub clinical hypothyroidism since last two years , with complaints such as weight gain, weakness, palpitation, hair fall , breathlessness, etc. The patient was put under ayurvedic treatment with drugs kaishore guggulu and dashamoola kwath, while maintaining pathya and apathya for three consecutive months. Monthly observation were done , after the complete duration of treatment the blood TSH level was successfully dropped from 8.5 to 4.3 milli international units / liter , with consecutive relief from aforesaid symptoms.